Estimativa de produção de biogás e potencial energético dos resíduos sólidos urbanos em Minas Gerais - Juliana Carvalho Figueiredo (2012)
Several Brazilian cities do not have proper management of urban solid waste, disposing it inappropriately. In addition to environmental and socioeconomical problems, the disposal of urban solid waste in non-controlled dump disposal sites hinders the use of the biogas generated during the decomposition process of the waste. Landfills can be seen as a way to reduce methane emissions, and also as an opportunity for energy generation. Hence, this work presents an estimate of the emission of biogas originated from the likely decomposition of solid waste in landfills at the Minas Gerais state, grouped in territorial arrangements. From modeling performed with the LandGEM model it is proposed four scenarios for the estimated biogas production and potential energy. In scenarios 1 and 2 the proposal is that all the MSW are lead to landfills. In scenarios 3 and 4, it is proposed to take the MSW from small municipalities to recycling/composting and pyrolysis, respectively. Values of biogas obtained in Scenario 1, where it was used the standard data from the World Bank, were found overestimated compared to the other three scenarios. In Scenario 2, using IPCC data, the potential energy estimated is about 45.5% of the value obtained in scenario1. In Scenario 3, there was a decrease of 21.3% on the potential energy. In Scenario 4, despite the estimated potential energy of the biogas meet the same level of Scenario 3, one can observe an increase in energy from the possibility of using the charred residue obtained by the pyrolysis process. It was observed an increase of 44.6% in the potential energy of Scenario 4, with the possibility of using the MSW charred product, surpassing by 12.2% the potential energy of Scenario 2.